Eradicating the Three Deadly Sins: Bullying, sexual violence, and intolerance in inclusive education in Banyumas Regency - Desta Riani, Aan; Suyanto, Edy; Retno Wulan, Tyas; Wuryaningsih, Tri; Chamadi, Muhamad Riza (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2025)
The challenges of inclusive education in Banyumas Regency, apart from the lack of special assistant teachers, the inclusive curriculum, and inadequate facilities are the three deadly sins of education: bullying, intolerance, and sexual violence. This research aims to analyze how inclusive schools address the issue of these three sins of education. This research employed qualitative methods through a case study at SDN (State Elementary School) 5 Arcawinangun and SD (Elementary School) Terpadu Putera Harapan Purwokerto. Data collection was done through interviews, observations, and FGDs. The results showed that bullying cases were the most dominating cases in education, followed by intolerance and sexual violence. Bullying cases were also experienced by children with special needs. The school has made various efforts to overcome this problem, including anti-bullying socialization for students both in the classroom, such as through songs that are easily understood by children, and outside the classroom, such as during the flag ceremony. In addition, the school is responsible for providing an understanding to all school members about the existence of children with special needs to provide appropriate and non-discriminatory educational services.